TRPA1 Ion Channel Determines Beneficial and Detrimental Effects of GYY4137 in Murine Serum-Transfer Arthritis - Bátai, István Z.; Sár, Cecília Pápainé; Horváth, Ádám; Borbély, Éva; Bölcskei, Kata; Kemény, Ágnes; Sándor, Zoltán; Nemes, Balázs; Helyes, Zsuzsanna; Perkecz, Anikó; Mócsai, Attila; Pozsgai, Gábor; et al. (Frontiers in Pharmacology, 2019)
Modulation of nociception and inflammation by sulfide in rheumatoid arthritis and activation of TRPA1 ion channels by sulfide compounds are well documented. The present study aims to investigate TRPA1-mediated effects of sulfide donor GYY4137 in K/BxN serum-transfer arthritis, a rodent model of rheumatoid arthritis. TRPA1, as well as somatostatin sst4 receptor wild-type and knockout mice underwent K/BxN serum transfer and were treated daily with GYY4137. Functional and biochemical signs of inflammation were recorded, together with histological characterization. These included detection of hind paw mechanical hyperalgesia by dynamic plantar esthesiometry, hind paw volume by plethysmometry and upside-down hanging time to failure. Hind paw erythema, edema and passive movement range of tibiotarsal joints were scored. Somatostatin release from sensory nerve endings of TRPA1 wild-type and knockout mice in response to polysulfide was detected by radioimmunoassay. Polysulfide formation from GYY4137 was uncovered by cold cyanolysis. GYY4137 aggravated mechanical hyperalgesia in TRPA1 knockout mice, but ameliorated it in wild-type ones. Arthritis score was lowered by GYY4137 in TRPA1 wild-type animals. Increased myeloperoxidase activity, plasma extravasation and subcutaneous MIP-2 levels of hind paws were detected in TRPA1 knockout mice upon GYY4137 treatment. Genetic lack of sst4 receptors did not alter mechanical hyperalgesia, edema formation, hanging performance, arthritis score, plasma extravasation or myeloperoxidase activity. TRPA1 WT animals exhibited smaller cartilage destruction upon GYY4137 administration. Sodium polysulfide caused TRPA1-dependent somatostatin release from murine nerve endings. Sulfide released from GYY4137 is readily converted into polysulfide by hypochlorite. Polysulfide potently activates human TRPA1 receptors expressed in CHO cells. According to our data, protective effect of GYY4137 is mediated by TRPA1 while detrimental actions are independent of the ion channel in the K/BxN serum-transfer arthritis model in mice. At acidic pH in inflamed tissue sulfide is released from GYY4137 and reacts with neutrophil-derived hypochlorite. Resulting polysulfide might be responsible for TRPA1-mediated antinociceptive, and anti-inflammatory as well as TRPA1-independent pro-inflammatory effects.